Effects of Written Corrective Feedback on College EFL Students’ Writing Accuracy and Linguistic Knowledge Acquisition - Sun, Haiyang; QI, Wenbo (Chinese journal of applied linguistics, 2022)
Set at the interface between second language acquisition and second language writing, this study examines how different types of written corrective feedback (WCF) influence the writing accuracy of Chinese college students learning English as a Foreign Language (EFL) and whether WCF facilitates the students’ grasp of the focused linguistic knowledge. The participants (n = 60) were divided into direct correction group (n = 20), indirect error-coding group (n = 20) and metalinguistic explanation group (n = 20). The three groups wrote four essays in two months and received WCF for the first three essays on the five targeted error types, namely tense errors, confusion of different forms of a word, word (articles, prepositions, etc.) missing, errors in subject-verb agreement and inappropriate verb-noun collocations. The results show that all three types of WCF improved students’ writing accuracy but none of them had any statistical advantage, and the metalinguistic WCF was more effective than the other two forms in facilitating the acquisition of the targeted linguistic features. These results shed some light on teaching and consolidation of language points through writing in EFL contexts.